Frecuencia e intensidad del viento en Zaragoza - Hernández Navarro, María Luz (Geographicalia, 2017)
This article studies the frequency and wind intensity al Zaragoza 'Aeropuerto" along the period 1957-86. It analyzes the mensual mean speed, the mean speed according to the compass rose, according to speed intervals, the percentage of calms, the maxim gust of wind and the daily mean speed along the period 1982-86.